Cimento de ionômero de vidro é melhor do que resina composta em restaurações classe II de dentes decíduos? Uma revisão sistemática com meta-análise. - Dias, Ana Giselle Aguiar [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The aim of the present study was to perform a systematic review and meta analysis (MA) on the clinical performance of glass ionomer cement (GIC) compared to composite resin (CR) in class II restorations in deciduous teeth. A comprehensive search was performed on the PubMeb, Scopus, Web of Science, LILACS BBO, Cochrane Library, Clinical Trials and OpenGrey databases, without dat e or language restrictions. Mesh terms, synonyms and key words were used, adapted for each database. Manual search was also performed on the list of references of the selected articles. Five randomized controlled trials and three non randomized clinical tr ials comparing the clinical performance (assessed by the presence of secondary caries lesions, marginal discoloration, marginal adaptation, anatomical shape, and retention and wear of restorative material) were included in class restorations II performed w ith GIC compared to RC restorations in deciduous teeth. Fifteen complete studies were read in full, of which 8 were included in qualitative (risk of bias) and quantitative synthesis (meta analysis). The heterogeneity ranged from low to moderate in the 12 M As from the 8 studies, with a follow up of 6 to 48 months (38 to 73%), with no significant difference between the two materials in the final analysis (overall effect). The risk difference (95% confidence interval, p value) between RC and GIC for failure wa s 0.03 ( 0.11 0.05; p = 0.41); for marginal adaptation was 0.01 ( 0.06 0.05; p = 0.8); for marginal discoloration it was 0.07 ( 0.11 0.26, p = 0.44), and for the anatomical form it was 0.00 ( 0.04 0.05; p = 0.84). Regarding the presence of seconda ry caries lesion, the corresponding value was 0.07 (0.02 0.12; p = 0.01). The overall risk difference for clinical performance was 0.03 ( 0.01 0.06, p = 0.17). For all the analyzed parameters, the exclusion of the studies with less than 24 months of fo llow up and the exclusion of non randomized studies did not influence the final result of the MA. However, the results were significantly influenced by the type of GIC (conventional or resin modified) and type of isolation (absolute or relative). It was co ncluded that resin modified GIC presented a clinical performance significantly higher than RC in relation to the prevalence of secondary caries lesions, whereas conventional GIC was similar to RC for this parameter. Regarding the whereas conventional GIC was similar to RC for this parameter. Regarding the percentage of marginal faipercentage of marginal failure, marginal adaptation, marginal discoloration and lure, marginal adaptation, marginal discoloration and anatomical shape, both materials presented similar performance, regardless of the anatomical shape, both materials presented similar performance, regardless of the type of GIC. Thus, the possibility of light curing along with its cariostatic properties, type of GIC. Thus, the possibility of light curing along with its cariostatic properties, indicate that resinindicate that resin--modified Gmodified GIC is the material of choice for class II restorations in IC is the material of choice for class II restorations in deciduous teeth.deciduous teeth.

O objetivo do presente estudo foi realizar uma revisão sistemática e meta-análise (MA) sobre o desempenho clínico do cimento de ionômero de vidro (CIV) comparado ao de resina composta (RC) em restaurações classe II em dentes decíduos. Foi realizada uma busca abrangente nas bases PubMeb, Scopus, Web of Science, LILACS-BBO, Cochrane Library, Clinical Trials e OpenGrey, sem restrições de data ou idioma. Foram utilizados termos Mesh, sinônimos e palavras chave, adaptados para cada base de dados. Também foi feita busca manual na lista de referências dos artigos selecionados. Foram incluídos 5 ensaios clínicos controlados e randomizados e 3 estudos clínicos não randomizados, que compararam o desempenho clínico, avaliado pela presença de lesões de cárie secundária, descoloração marginal, adaptação marginal, forma anatômica e retenção e desgaste do material restaurador de restaurações de classe II realizadas com CIV em comparação com restaurações de RC em dentes decíduos. Quinze estudos completos foram lidos na íntegra, dos quais 8 foram incluídos na síntese qualitativa (risco de viés) e quantitativa (meta-análise). A heterogeneidade variou de baixa a moderada nas 12 MAs realizadas dos 8 estudos, com acompanhamento de 6 a 48 meses (38 a 73%), não havendo diferença significativa entre os dois materiais na análise final (overall effect). A diferença de risco (intervalo de confiança 95%; valor de p) entre RC e CIV quanto a falhas foi de -0,03 (-0,11 – 0,05; p= 0,41); quanto a adaptação marginal, -0, 01 (-0,06 – 0,05; p= 0.8); quanto a descoloração marginal, 0,07 (-0,11 – 0, 26; p=0,44), quanto a forma anatômica, 0,00 (-0,04 – 0,05; p= 0,84); e quanto a presença de lesão de cárie secundária foi de 0,07 (0,02 – 0,12; p= 0,01). A diferença de risco geral para o desempenho clínico foi 0,03 (-0,01 – 0,06; p= 0,17). Para todos os parâmetros analisados, a exclusão de um estudo com menos de 24 meses de acompanhamento e dos estudos não randomizados não influenciou no resultado final da MA. Entretanto, os resultados foram significativamente influenciados pelo tipo de CIV (convencional (n=2) ou modificado por resina (n= 6) e tipo de isolamento (absoluto (n=6) ou relativo (n=2)). Concluiu-se que o CIV modificado por resina apresentou desempenho clínico significativamente superior a RC em relação à prevalência de lesões de cárie secundária, enquanto que o CIV convencional se mostrou semelhante à RC para este parâmetro. Quanto à porcentagem de falhas, adaptação marginal, descoloração marginal e forma anatômica, ambos os materiais apresentaram desempenho semelhante, independente do tipo de CIV. Assim, a possibilidade de fotopolimerização, somada às suas propriedades cariostáticas, indicam que o CIV modificado por resina é o material de escolha para restaurações classe II em dentes decíduos.
Does glass ionomer cement is better than composite resin in class II primary teeth restorations? A systematic review with meta analysis.
Keywords: Composite resins; Criança; Restauração dental; Dentes decíduos; Cimentos de ionômero de vidro; Resinas compostas